2016
DOI: 10.7205/milmed-d-15-00404
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Military Sexual Trauma: A Mixed-Methods Study of Women Veterans' Experiences Who Served From World War II to the War in Afghanistan

Abstract: Since 2004, there has been increased effort to reduce military sexual trauma (MST) in the U.S. military. Although MST covers a range of inappropriate behaviors, the majority of research, treatment, and outreach are focused on sexual assault and the experiences of individuals serving in Afghanistan and Iraq. During a study on veterans' involvement in a national peace organization, participants were asked about their military experiences. Veterans served from World War II to current conflicts in Iraq and Afghani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 38 publications
1
39
1
Order By: Relevance
“…Individuals who must continue to be in situations or contexts with the perpetrator and/or institution may be particularly susceptible to betrayal blindness—the tendency to minimize or ignore information in order to preserve the relationship with the institution as a means of survival (Freyd, , ); this may facilitate continuing to be identified with the institution. It is also possible that individuals who experienced institutional betrayal following MST felt compelled or opted to discharge from the military (Katz, Huffman, & Cojucar, ; Monteith, Gerber, Brownstone, Soberay, & Bahraini, ; Morral et al, ; Wolff & Mills, ), potentially due to perceptions that the military failed to protect them from the sexual trauma or did not promote a supportive and safe environment.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who must continue to be in situations or contexts with the perpetrator and/or institution may be particularly susceptible to betrayal blindness—the tendency to minimize or ignore information in order to preserve the relationship with the institution as a means of survival (Freyd, , ); this may facilitate continuing to be identified with the institution. It is also possible that individuals who experienced institutional betrayal following MST felt compelled or opted to discharge from the military (Katz, Huffman, & Cojucar, ; Monteith, Gerber, Brownstone, Soberay, & Bahraini, ; Morral et al, ; Wolff & Mills, ), potentially due to perceptions that the military failed to protect them from the sexual trauma or did not promote a supportive and safe environment.…”
Section: Discussionmentioning
confidence: 99%
“…Underreporting of sexual offences is common in civilian populations but reasons for this may differ. Fear, cohesive behaviour of perpetrators and command structures may delay or prevent reporting in the military21 22 and retaliation was experienced by two-thirds of US women reporting sexual assault 5. Support from leaders can, however, moderate the relationship between trauma exposure and outcomes 23.…”
Section: Military-specific Featuresmentioning
confidence: 99%
“…How MST is reported, and the treatment of those who report MST is an area of concern. In particular, there is a perception that investigations carried out by the military are far from proficient and women service personnel fear reprisals for reporting incidents (Wolff & Mills, 2016). It is argued that both of these factors contribute to a potential underreporting of incidents.…”
Section: Experiences During the Militarymentioning
confidence: 99%
“…It is argued that both of these factors contribute to a potential underreporting of incidents. The study by Wolff and Mills (2016) specifically focused on the reporting of MST from WWII onwards. They found that MST had affected 90% of women participants in that study, yet only 15% had reported it.…”
Section: Experiences During the Militarymentioning
confidence: 99%
See 1 more Smart Citation